Does Internet Censorship Reduce Crime Rate? - Karnadi, Erwin Bramana (Bina Nusantara University, 2015)
The study examines the relationship between Internet censorship and crime rate. Classical views of censorship suggest that filtering contents that are per- ceived as negative such as violence and pornography can have a negative impact on crime rate. However, there is no evidence to suggest any causal relationship between censorship and crime rate. The Internet has made it easier for individuals to access any information they want, and hence Internet Censorship is applied to filter contents that are deemed negative. We discussed several approaches that may be used to estimate the relationship between Internet Censorship and Crime Rate, and we decided to use OLS. We found that Conflict Internet Censorship is the only type of Internet censorship that has a significant negative impact on Crime Rate. Furthermore, it only significantly affects Crime Rate for highly educated countries.